Referrals to, and characteristics of patients attending a specialist hypertension clinic - Kennedy, Cormac; Hennessy, Martina (My University, 2022)
The management of hypertension is suboptimal in Ireland and internationally. The role of a specialist hypertension clinic is not always defined but an analysis of the reasons for referral are likely informative. Also, a description of the clinical characteristics of patients with hypertension will inform requirements for comprehensive hypertension management in the community and secondary care. Patients were recruited at consecutive hypertension clinics at St James Hospital, Dublin from July to September 2019. Reasons for referral, clinical characteristics of patients, their investigations and treatment were analyzed. 236 patients were included in the study. The majority of patients, 83%, were obese or overweight. A family history of hypertension was a frequent finding with 70.8% of patients reporting same. 26.7% of patients were under the age of 40. 78% of referrals were from primary care and the most referrals were to investigate secondary causes of hypertension or because the patient was ≤40 years of age. Calcium channel blockers were the treatment most frequently prescribed (51.7%). Clinic blood pressure for the cohort was 137/81 mmHg and this was replicated by their ambulatory BP. This insight into the contemporary management of hypertension highlights the frequency of obesity and a positive family history in those with hypertension. Most referrals were consistent with international guidance though deviations were evident. Findings suggest a national program for hypertension with greater focus on public health interventions and better resourcing of primary care is required.
PUBLISHED